Case Report: Clinical application of immunotherapy-based combination regimen in primary osteosarcoma of the uterus - Yang, Jing; Chen, Xiaowen; Li, Xiaofang; Liu, Wenci; Liao, Sihai; Wang, Yuzhou; Zuo, Yufang (Frontiers in Oncology, 2023)
Primary osteosarcoma of the uterus is an extremely rare pure heterologous sarcoma of the uterus. The available information is limited to case reports. To date, only 31 cases of this type of cancer have been reported. Here, we report the first clinical experience of an immunotherapy-based combination regimen for multiple metastatic primary osteosarcoma of the uterus. The patient had undergone multiple treatments prior to this regimen, but her condition continued to progress. However, After 3 cycles of immunotherapy combined with targeted therapy and chemotherapy, review showed that the disease was stable and even in partial remission. The patient has a good quality of life and is expected to survive for a long time.